2017
DOI: 10.1038/s41598-017-06119-w
|View full text |Cite
|
Sign up to set email alerts
|

β-caryophyllene emitted from a transgenic Arabidopsis or chemical dispenser repels Diaphorina citri, vector of Candidatus Liberibacters

Abstract: Production of citrus, the main fruit tree crop worldwide, is severely threatened by Huanglongbing (HLB), for which as yet a cure is not available. Spread of this bacterial disease in America and Asia is intimately connected with dispersal and feeding of the insect vector Diaphorina citri, oligophagous on rutaceous host plants. Effective control of this psyllid is an important component in successful HLB management programs. Volatiles released from the non-host guava have been shown to be repellent to the psyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 52 publications
1
45
0
1
Order By: Relevance
“…As described above, the ubiquitous volatile terpene ( E )‐β‐caryophyllene repels a number of agriculturally important pests, including psyllids (Zhang et al ., ). Intercropping (with the ( E )‐β‐caryophyllene emitting guave) or possibly the application of ( E )‐β‐caryophyllene dispensers may provide solutions for this enormous agricultural problem (Mafra‐Neto et al ., ; Alquézar et al ., ) (Figure f).…”
Section: Agricultural Importance Of Vocsmentioning
confidence: 95%
See 2 more Smart Citations
“…As described above, the ubiquitous volatile terpene ( E )‐β‐caryophyllene repels a number of agriculturally important pests, including psyllids (Zhang et al ., ). Intercropping (with the ( E )‐β‐caryophyllene emitting guave) or possibly the application of ( E )‐β‐caryophyllene dispensers may provide solutions for this enormous agricultural problem (Mafra‐Neto et al ., ; Alquézar et al ., ) (Figure f).…”
Section: Agricultural Importance Of Vocsmentioning
confidence: 95%
“…(f) ( E )‐β‐caryophyllene repels HLB transmitting Diaphorina citri . Naturally ( E )‐β‐caryophyllene emitting plant species such as guave, the use of ( E )‐β‐caryophyllene dispensers and metabolic engineering of ( E )‐β‐caryophyllene production can potentially be used to protect citrus trees against HLB (Mafra‐Neto et al ., ; Alquézar et al ., ).…”
Section: The Role Of Vocs In Pollinationmentioning
confidence: 97%
See 1 more Smart Citation
“…Terpenoids are the most abundant compounds in plant volatiles. Sesquiterpenes and monoterpenes, such as (E)-α-bergamotene, (E)-β-caryophyllene, linalool, etc., are reported to generally have an effect on an insect's feeding orientation [94][95][96][97]. Many pathogens manipulate these chemical volatiles to alter their vectors' behaviors, especially insect-borne plant viruses, whose spread is highly reliant on insect vectors [2,98,99].…”
Section: Ja-regulated Chemical Defense Hijacked By Plant Virusesmentioning
confidence: 99%
“…β-caryophyllene is the main constituent, with β-Ocimene, of a volatile blend known to increase capture of D. citri on yellow sticky traps (Patt and Setamou, 2010). However, when tested as an isolated compound in olfactometers, conflicting results were reported; Mann et al (2012) did not find any significant response associated to β-caryophyllene at 5 µg/µl, whereas Alquézar et al (2017) found it to repel D. citri at 1 and 10 µg/µl. In other systems, plant pathogen infection induced increased release of β-caryophyllene.…”
Section: Discussionmentioning
confidence: 99%